Daughter of darkness - Brooks, Terry (Waterville, Maine Thorndike Press, a part of Gale, a Cengage Company, 2023)
"The thrilling second novel of an all-new fantasy series from the legendary author behind the Shannara saga, about a human girl adapting to her place in a magical world she's only recently discovered It's been two years since Auris escaped from the sinister Goblin prison and learned of her heritage as one of the Fae. She is now happily partnered with her Fae lover, Harrow, and deeply bonded with her new family. All seems to be going perfectly--until, surprisingly, the Goblin attacks begin again. Someone, it seems, has not forgotten that Auris exists and seems determined to retrieve her . . . but who? And why? As Auris begins to dig deeper into the mystery, old friends and new enemies appear, and she starts to realize that her still-shrouded past must contain the answers she needs. But even Auris does not suspect how far down the rabbit hole she is about to go, until Harrow is taken and an impossible ransom demand is issued. With two new companions at her side, Auris must attempt to unlock the remaining secrets of her past. For if she cannot, she will never see Harrow alive again"--
111431
Keywords: Magic -- Fiction; Fairies -- Fiction; Goblins -- Fiction; Dragons -- Fiction; Large type books; Fantasy fiction; Novels